Pediatric Thoracic Duct Injury: A Case Report - Ersöz, Nihat; Özokutan, Bülent Hayri; Yılmaz, Mustafa; Celkan, Adnan; Ceylan, Haluk (Fırat University, 2006)
Traumatic injury of thoracic duct is very rare in children. It usually develops due to trauma or as a complication of chest surgery. Preoperative diagnosis is especially difficult in traumatic injury and is diagnosed during surgery. Conservative or surgical treatments may be therapuetic options. Conservative treatment is preferred in smaller injuries and complications can be observed in long lasting treatments. As a surgical treatment, primary repair, anastomozis, or ligation of duct can be preferred. Since thoracic duct is smaller in children, primer surgery is not recommended. Here we present a seven-year old boy who has injury of thoracic duct due to firearm injury. In this case, injury was observed during emergency laparatomy and it was repaired primarily. In postoperative period, control lymphoid scintigraphy showed lymphoid flow and there was no lymphoid leakage. Postoperative period is uneventful and the patient was discharged without any complication. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Çocuklarda travmatik duktus torasikus yaralanması nadir görülür. Genellikle travmaya bağlı gelişir veya göğüs cerrahisi ameliyatlarında iatrojenik olarak oluşur. Özellikle travmaya bağlı oluşan yaralanmaların ameliyat öncesi saptanması güç olup, ancak operasyon esnasında tanı konulmaktadır. Tedavi konservatif ve cerrahi olarak yapılabilir. Konservatif tedavi daha çok küçük yaralanmalarda tercih edilir ve uzun süreli tedavide komplikasyonlar görülebilir. Cerrahi tedavide ise primer onarım, duktusun ligasyonu ve anastomoz tercih edilmektedir. Çocuklarda duktus çapının küçük olması nedeniyle primer onarımın yapılması önerilmemektedir. Ateşli silahla yaralanmaya bağlı duktus torasikus yaralanması olan 7 yaşında bir olgu sunuyoruz. Acil laparatomi yapılan hastada duktus torasikusta yaralanma tesbit edilerek bu bölge primer olarak onarıldı. Postoperatif dönemde kontrol amacıyla çekilen lenf sintigrafisinde lenf akımının olduğu ve lenf kaçağının bulunmadığı tesbit edildi. Postoperatif takipte herhangi bir komplikasyon görülmeyen olgumuz şifa ile taburcu edildi. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Çocukta Duktus Torasikus Yaralanması: Olgu Sunumu